(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the distribution of traditional Chinese medicine syndrome types and clinical characteristics in patients with premature ejaculation. Methods: A case series study was conducted on 299 premature ejaculation patients at the First Affiliated Hospital of Guangzhou University of Chinese Medicine from May 2023 to February 2024. Patients meeting ISSM (2014) criteria were classified into four traditional Chinese medicine syndromes: unconsolidation of kidney-qi, liver depression and kidney deficiency, downward dampness-heat, and yin deficiency with fire hyperactivity. Data on age, disease duration, premature ejaculation type, PEDT score, and comorbid erectile dysfunction were collected and compared between primary and secondary premature ejaculation. Results: The mean age was 32.16 ± 7.17 years, 83.61% under 40. The predominant syndrome was unconsolidation of kidney-qi (75.93%), followed by liver depression and kidney deficiency (12.37%), downward dampness-heat (7.02%), and yin deficiency with fire hyperactivity (4.68%). No significant difference in traditional Chinese medicine syndrome distribution was observed between primary and secondary premature ejaculation (p = 0.464). PEDT scores were significantly higher in primary premature ejaculation (p < 0.001). Conclusion: Unconsolidation of kidney-qi is the dominant traditional Chinese medicine syndrome in premature ejaculation patients. Primary and secondary premature ejaculation share similar syndrome patterns but differ in PEDT scores. These findings support traditional Chinese medicine syndrome differentiation for individualized premature ejaculation management.